Trypanosoma brucei multi-aminoacyl-tRNA synthetase complex formation limits promiscuous tRNA proofreading - Watkins, Rylan R.; Vradi, Anna; Shulgina, Irina; Musier-Forsyth, Karin (Frontiers in Microbiology, 2024)
Faithful mRNA decoding depends on the accuracy of aminoacyl-tRNA synthetases (ARSs). Aminoacyl-tRNA proofreading mechanisms have been well-described in bacteria, humans, and plants. However, our knowledge of translational fidelity in protozoans is limited. Trypanosoma brucei (Tb) is a eukaryotic, protozoan pathogen that causes Human African Trypanosomiasis, a fatal disease if untreated. Tb undergoes many physiological changes that are dictated by nutrient availability throughout its insect-mammal lifecycle. In the glucose-deprived insect vector, the tsetse fly, Tb use proline to make ATP via mitochondrial respiration. Alanine is one of the major by-products of proline consumption. We hypothesize that the elevated alanine pool challenges Tb prolyl-tRNA synthetase (ProRS), an ARS known to misactivate alanine in all three domains of life, resulting in high levels of misaminoacylated Ala-tRNAPro. Tb encodes two domains that are members of the INS superfamily of aminoacyl-tRNA deacylases. One homolog is appended to the N-terminus of Tb ProRS, and a second is the major domain of multi-aminoacyl-tRNA synthetase complex (MSC)-associated protein 3 (MCP3). Both ProRS and MCP3 are housed in the Tb MSC. Here, we purified Tb ProRS and MCP3 and observed robust Ala-tRNAPro deacylation activity from both enzymes in vitro. Size-exclusion chromatography multi-angle light scattering used to probe the oligomerization state of MCP3 revealed that although its unique N-terminal extension confers homodimerization in the absence of tRNA, the protein binds to tRNA as a monomer. Kinetic assays showed MCP3 alone has relaxed tRNA specificity and promiscuously hydrolyzes cognate Ala-tRNAAla; this activity is significantly reduced in the presence of Tb alanyl-tRNA synthetase, also housed in the MSC. Taken together, our results provide insight into translational fidelity mechanisms in Tb and lay the foundation for exploring MSC-associated proteins as novel drug targets.